(untitled) (Global Business Management Review (GBMR), 2021)
Innovative behaviour is attracted research interest. The research draws on Theory of Planned Behaviour (TPB) and Diffusion of Innovation (DOI) frameworks to examine the impacts of technology factors and intention to adopt Cloud-based Human Resource Management Systems on innovative behaviour. The mediating variable of intention to adopt Cloud-based HRMS was examined. Data were collected and analysed from 366 full-time employees who are working within the information and communication sector in SMEs in Jordan. The outputs from smart partial least square (SmartPLS) analysis reveal that technology factors effects intention to adopt Cloud-based HRMS, which consequently affects innovative behaviour. Whereas, leadership support was found to play a significant role in the relationship between intention to adopt Cloud-based HRMS and innovative behaviour, it has a positive effect. These results provide the relevance of the technological factor on how to foster innovative behaviors through intention to adopt Cloud-based HRMS and leadership support.